Chemical treatment ideal soaking time of empty fruit bunch (EFB) polymer composite to achieve high mechanical properties - Keegan Pereira A/L, Victor (Universiti Malaysia Sarawak (UNIMAS), 2008)
Palm oil empty fruit bunch natural fibre reinforced unsaturated polyester composite have been fabricated in random orientation with 10% constant fibre volume fraction. The experimental study was taken to determine the ideal soaking time of fibre during chemical treatment process with two different chemical agents (NaOH and Silane) to achieve highest value of Ultimate tensile strength, Modulus of elasticity and Energy Absorbed at Break. The specimens were categorized according to time frame for each chemical agent. Tensile test has been carried out to the entire specimen according to ASTM 3039-76 in order to investigate the behavior of the composite under tension. The Testometric machine been used to carried out this testing. The effect of the surface treatment by the chemical agent differs from one soaking time to another. The chemical treatment process purpose is to increase the roughness of the natural fibre for a better impregnation with matrix. The result showed that the ideal time to achieve highest ultimate tensile strength is at 4 days for NaOH and 2 minutes for Silane. The ideal time to achieve highest Young’s modulus value is at 3 day’s for NaOH and 5 minutes. Soaking time 2 day’s for NaOH and 15 minutes for Silane are the ideal time to achieve highest energy at break value.